Pharmacovigilance analysis of polatuzumab plus bendamustine and rituximab treatment protocol: identifying comprehensive safety signals using FDA database - Wu, Fang; Wang, Siliang; Xu, Xihui; Zhang, Weihui; Zhou, Jie; Niu, Runyan; Cai, Wenting; Yang, Yonggong; Liu, Mengying; Zhang, Jinping (Frontiers in Pharmacology, 2025)
BackgroundThe combination of polatuzumab, bendamustine and rituximab (pola+BR) was authorized for the treatment of relapsed or refractory Diffuse large B cell lymphoma (DLBCL). This study used the FDA database to identify safety signals related to the treatment protocol.MethodsThe adverse events (AEs) from 2019Q1 to 2023Q3 were analyzed by calculating the reporting odds ratio. Severe and non-severe cases were compared using either an independent samples t-test or chi-squared (χ2) test. Additionally, a score sheet was employed to prioritize the signals.ResultsIn all database, 58 significant signals were detected within 1,597 patients accepting the treatment protocol. Common AEs like neutropenia, thrombocytopenia, and peripheral neuropathy, as well as other AEs like anaemia, sepsis, cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome (ICANS) were a major focus. In addtion, 51.7%, 45.6% and 1.7% were sorted into low, moderate and high priority in term of clinical importance, respectively. Unexpected significant signals included intestinal obstruction, epilepsy, deep vein thrombosis, haemorrhage, increased blood lactate dehydrogenase and hypercalcemia.ConclusionOur study identified significant AE signals for pola+BR through realworld disproportionality analysis data and analyzed the severity and clinical priority of these signals, which can assist clinicians in managing related AEs.